Green Street a sustainable flood mitigation system in the University Belt, Manila - Buitre, Marian Alisa L.; Villajuan, Jose Dan (Quezon City College of Architecture, University of the Philippines Diliman, 2020)
Rapid urbanization is a consequence of human activities and has brought peril in one area to another; such as pollution and flooding. Not only does it bring environmental issues, but health issues as well. This has led to the decrease of open spaces in the city to accommodate the rise of population, hence making urban areas as dense as it can be. Because of this, more and more buildings are built, and green areas decrease. According to the Minnesota Stormwater Manual (2005), bioretention has become one of the best used stormwater management practices for addressing pollution and flooding in urban areas and urbanized watersheds. In this manual, the factors that affect flooding are dam overflow, lack of evaporation surfaces, nearby sludge dumping and open dumpsites. On the other hand, the University Belt in Manila is one of the many areas that has constantly been affected by the flooding waters of Metro Manila and it has been a major adversity since most of the affected are students. Due to the flood trend, the thesis aims to reduce the flooding through the application of bioretention systems. According to the aforementioned manual, bioretention can be incorporated in many ways. In this study, the focus would be the incorporation of bioretention in the screetscapes of the University Belt. It will study the following variables: vegetation, hardscape, rain water fall. This study also aims to provide vegetation computation that can be used to control flood. Together with this, the study will also consider standard streetscape criteria, and permeable pavement incorporation. The use of Bioretention Streetscapes is then used to solve the issue of flooding in urban areas.
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines Diliman
Keywords: Flood Control -- University Belt (Manila).; Rapid Urbanization -- University Belt (Manila).; Stormwater